Analisis Asupan Karbohidrat dan Lemak pada Dewasa Muda dengan Obesitas Sentral di Fakultas Kedokteran Universitas Riau - Nurhasanah Nurhasanah; Imelda Tresia Pardede; Feriyandi Nauli; Istiyana Hayati; Fikri Roja Nasution; Angga Rizki Hermawan (Jurnal Ilmu Kedokteran, 2022)
Central obesity is a state of the body characterized by the accumulation of excess fat in the abdominal area and is a component of the metabolic syndrome and plays an important role in the pathogenesis of cardiovascular disease and cancer. The main causes of central obesity are the wrong diet such as a diet high in fat and carbohydrates and low in fiber. The purpose of this study was to analyze carbohydrate and fat intake in young adults with central obesity. This research was an analytical study with a cross-sectional approach. The Sampling techniques used the purposive sampling method with a sample of 66 people consisting of 33 central obese people and 33 central non-obese people. The results of this study showed that the average consumption of carbohydrates in a day on central obesity is higher (341,74 g/day) than the consumption of carbohydrates in non-central obesity (263,26 g/day) and the average consumption of fat in a day on central obesity is higher (167.2 g/day) than the consumption of fats of non-central obesity (100,3 g/day). There was a significant difference in carbohydrate intake and fat intake between the group of young adults with central obesity and non-central obesity (p=0.000).